2017
DOI: 10.1038/s41598-017-00610-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the interaction of UBA5 with UFM1 via a UFM1-interacting sequence

Abstract: The modification of proteins by ubiquitin-fold modifier 1 (UFM1) is implicated in many human diseases. Prior to conjugation, UFM1 undergoes activation by its cognate activating enzyme, UBA5. UBA5 is a non-canonical E1 activating enzyme that possesses an adenylation domain but lacks a distinct cysteine domain. Binding of UBA5 to UFM1 is mediated via an amino acid sequence, known as the UFM1-interacting sequence (UIS), located outside the adenylation domain that is required for UFM1 activation. However, the prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…Previously, we and others have shown that the adenylation domain by itself is unable to activate UFM1, but a fragment possessing both the adenylation domain and the UIS successfully activates UFM1 [2,30]. Interestingly, although UBA5 dimerization is critical for UFM1 activation, UBA5 is not a stable dimer in solution.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Previously, we and others have shown that the adenylation domain by itself is unable to activate UFM1, but a fragment possessing both the adenylation domain and the UIS successfully activates UFM1 [2,30]. Interestingly, although UBA5 dimerization is critical for UFM1 activation, UBA5 is not a stable dimer in solution.…”
Section: Introductionmentioning
confidence: 79%
“…Ubiquitin fold modifier 1 (UFM1) is a ubiquitin-like protein (UBL) that shares the β-grasp fold of ubiquitin even though it has only 16% sequence identity with ubiquitin [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Atg8 does not bind simultaneously to those 2 domains but, rather, first to the C‐terminal helical domain and then to the adenylation domain where Atg8 adenylation and the thioester bond formation take place. In contrast to Atg7, human UBA5 does not have a helical domain, but rather an ~13 aa sequence‐ located C‐terminal to the adenylation domain that serves as a UFM1‐interacting sequence (UIS) (2325). Human UBA5 has 2 isoforms, both of which have the adenylation domain and the UIS, but only 1 has an extension of 56 aa N‐terminal to the adenylation domain, which was previously shown not to be essential for UBA5 activity (26, 27).…”
mentioning
confidence: 99%
“…However, Atg8 does not bind simultaneously to those 2 domains but, rather, first to the C-terminal helical domain and then to the adenylation domain where Atg8 adenylation and the thioester bond formation take place. In contrast to Atg7, ABBREVIATIONS: Atg, autophagy-related; HEPES, 4-(2-hydroxyethyl)-1piperazineethanesulfonic acid; ITC, isothermal titration calorimetric; K d , dissociation constant; SEC-MALS, size-exclusion chromatography with multiangle light scattering; UBA5, ubiquitin like modifier-activating enzyme 5; UBL, ubiquitin-like protein; UFC1, ubiquitin-fold modifier conjugating enzyme 1; UFL1, Ufm1 specific ligase 1; UFM1, ubiquitin fold modifier 1; UIS, UFM1-interacting sequence; WT, wild type human UBA5 does not have a helical domain, but rather an ;13 aa sequence-located C-terminal to the adenylation domain that serves as a UFM1-interacting sequence (UIS) (23)(24)(25). Human UBA5 has 2 isoforms, both of which have the adenylation domain and the UIS, but only 1 has an extension of 56 aa N-terminal to the adenylation domain, which was previously shown not to be essential for UBA5 activity (26,27).…”
mentioning
confidence: 99%